Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Problem-Based Learning di Kelas V SDN 45 Bungo Pasang, Kota Padang - Tiarani, Siti Dhinda; Waldi, Atri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research aims to elucidate how the improvement of learning outcomes is achieved by implementing the Problem Based Learning (PBL) model in Pancasila Education for the fifth grade at SDN 45 Bungo Pasang Padang City, integrated within the context of the Merdeka Curriculum. This Classroom Action Research utilizes a combined qualitative and quantitative approach. The research subjects are 15 students in the fifth grade of SDN 45 Bungo Pasang Padang City during the January-June semester of the academic year 2023/2024. The research findings include: First, in the development of teaching modules during Cycle I, there was an increase in the average percentage from 89.55% (B) to 95.8% (SB) in Cycle II. Second, the implementation of teaching from the teacher's aspect increased from 91% (SB) in Cycle I to 96.4% (SB) in Cycle II. Third, the implementation results from the student's aspect increased from 91% (SB) in Cycle I to 96.4% (SB) in Cycle II. Fourth, the students' learning outcomes increased from an average of 86.2 (B) in Cycle I to 95.3 (SB) in Cycle II. In conclusion, the PBL model can enhance students' learning outcomes in Pancasila Education for the fifth grade at SDN 45 Bungo Pasang, Padang City.